Targeted pH switched europium complexes monitoring receptor internalisation in living cells. Issue 47 (18th May 2021) - Fradgley, Jack D.; Starck, Matthieu; Laget, Michel; Bourrier, Emmanuel; Dupuis, Elodie; Lamarque, Laurent; Trinquet, Eric; Zwier, Jurriaan M.; Parker, David
Abstract : We report the design and evaluation of pH responsive luminescent europium(iii ) probes that allow conjugation to targeting vectors to monitor receptor internalisation in cells. Abstract : We report the design and evaluation of pH responsive luminescent europium(iii ) probes that allow conjugation to targeting vectors to monitor receptor internalisation in cells. The approach adopted here can be used to tag proteins selectively and to monitor uptake into more acidic organelles, thereby enhancing the performance of time-resolved internalisation assays that require pH monitoring in real time.